Pengaruh Citra Merek, Kesadaran Merek, dan Loyalitas Merek Terhadap Proses Keputusan Pembelian Kopi Janji Jiwa di Kota Bandung - Damayanti, Maria Cyntia; Hasbi, Imanuddin (Universitas Batanghari Jambi, 2024)
In the current era, drinking coffee is a trend that is carried out by almost all groups, especially among young people. Coffee is part of the lifestyle of modern society so that coffee is a very popular drink in the world, including in Indonesia. Kopi Janji Jiwa is the most popular coffee shop in Indonesia by being ranked first out of seven other coffee shops. Janji Jiwa until now has more than 800 outlets spread across cities in Indonesia including in Bandung. The main objective of this study was to determine the effect of brand image, brand awareness, and brand loyalty on the buying decision process of Kopi Janji Jiwa in Bandung City. The type of research used in this study is a quantitative method. The sampling technique uses nonprobability sampling with purposive sampling in which the number of respondents is 385 people. In this study using multiple linear regression data analysis techniques were processed using IBM SPSS Version 26. Based on the results of the descriptive analysis, it shows that each variable in this study as a whole is in the good category. All of the independent variables are brand image, brand awareness, and brand loyalty and have a positive and significant influence on the dependent variable, namely the purchasing decision process.